Factores motivacionales en los trabajadores de la Municipalidad Distrital de Fernando Lores, 2022 - Cabanillas Vasquez, Jary Nery (2023)
The present study's general objective was to identify which motivational factors the employees of the administration and planning management of the district municipality of Sargento Lores attach greater importance to, within the framework of Frederick Herzberg's two-factor theory; For this purpose, a non-experimental descriptive design was applied to the total number of workers of said managements; for which the survey technique was obtained through a questionnaire with three parts: in the first they were asked about the degree of importance they attach to motivational factors, in the second about their current level of motivation, and in the third on what factors your employing entity currently prioritizes or applies. The data obtained were processed in the Excel program, yielding the following results: the factors to which the workers attach the greatest importance are the intrinsic or motivating factors, particularly those of achievement and responsibility for work with a score higher than five on a scale of maximum 8 points; and to which they attach less importance are the hygienic or extrinsic factors of relationships and working conditions, with an average score of 4.